Efficacy of collagen matrix seal and collagen sponge on ridge preservation in combination with bone allograft: A randomized controlled clinical trial. (26th May 2017) - Natto, Zuhair S.; Parashis, Andreas; Steffensen, Bjorn; Ganguly, Rumpa; Finkelman, Matthew D.; Jeong, Y. Natalie
Abstract: Aim: To test whether the use of collagen matrix seal (CMS) results in similar hard and soft tissue remodelling to that with collagen sponge (CS) used as barriers 4 months following alveolar ridge preservation (ARP), in combination with freeze‐dried bone allograft (FDBA). Materials and methods: Twenty‐eight patients were randomly assigned to the two groups. Clinical and radiographic measurements were recorded with the same stent at baseline and 4 months for standardization. The flapless technique following a traumatic extraction was used for the two types of barriers. Results: All patients completed the study, 14 in the CMS group and 14 in the CS group. Reduction in coronal ridge width (1.21 mm‐14.91% CMS and 1.47 mm‐20.40% CS) and vertical buccal bone resorption (0.30 mm CMS and 0.79 mm CS) were not significantly different. A slight increase in buccal gingival thickness at the coronal part was observed in both groups (0.9 mm CMS and 0.5 mm CS). Conclusions: Collagen matrix seal and CS, when combined with FDBA, significantly minimized ridge resorption in all dimensions and maintained buccal soft tissue thickness in sockets with a buccal plate loss of <2 mm in comparison to previously reported findings recorded after tooth extraction without ARP.